Geographic ranges of reef corals (Cnidaria: Anthozoa: Scleractinia) in the Indo‐Pacific: Ecological Archives E094‐150. Issue 7 (1st July 2013) - Hughes, Terry P.; Connolly, Sean R.; Keith, Sally A.
Abstract: Information on geographic ranges and the location of range boundaries of individual species is key to studies of biogeography, evolution, macroecology, and conservation biology. Traditionally, marine biogeography has emphasized patterns in contours of species or generic richness, based on counts of species collected from different locations. To understand more fully why these and other patterns occur requires data on the geographic extent of individual species, and how their ranges overlap. We compiled a spatial database of geographic range boundaries from the primary literature and from our own records for Indo‐Pacific reef‐building scleractinian corals (726 species in 17 families: Acroporidae, Agariciidae, Astrocoeniidae, Caryophylliidae, Dendrophylliidae, Euphyllidae, Faviidae, Fungiidae, Meandrinidae, Merulinidae, Oculinidae, Pocilloporidae, Poritidae, Mussidae, Pectiniidae, Siderastreidae, and Trachyphylliidae). Corals have strongly skewed range distributions, with many species being pandemics. The data show little support for Rapoport's Rule (smaller ranges near the equator) or for the more general hypothesis that range sizes are smaller, on average, where species richness peaks. The unusual disparity between species richness and endemicity in locations such as the Coral Triangle hotspot challenges conservation priorities that tend to focus on hotspots and neglect depauperate locations. The empirically observed locations of ranges diverge from predictions of mid‐domain models in ways that are consistent with the hypothesis that westward‐flowing equatorial currents influence the species distributions of Indo‐Pacific corals. The spatial database also can be used to examine species turnover at faunal boundaries, facilitating new studies that can explore barriers to dispersal and the evolution of geographic range size.